FAKTOR-FAKTOR YANG MENGHALANGI PELAKSANAAN PERJANJIAN DALAM PEMBERIAN KREDIT PROPERTI - Roy Thery (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
Abstract         Starting from the issuance of Law No. 4 of 1996 on security rights over the land and objects relating to land (Act Encumbrance) on April 9, 1996. The Act which is the implementing regulations of the institution as security rights over land mandated by Article 51 of Law No. 5 of 1960 on the Basic Regulation of Agrarian Principles (BAL), which contains several provisions that could be called as an important breakthrough.            One of the provisions is quite prominent is the permissibility of land status on the State Land Use Right as collateral or encumbered Mortgage. For the community and business property, such provision is of course very positive. The people holding the right to use can improve the economy, because they can utilize the credit facilities from financial institutions to develop their business. While the Housing Development Company (Developer), also greatly helped by this provision. First, because the right to use the land already has economic value. Secondly, there is no obstacle for the developer to expand the market or sell the property that they built on the land-use rights to foreigners.